Raised bed planting for boosting soybean yields and profits - K P, Jaseem; Meena, Vijay Singh; Hasanain, Mohammad; Meena, Sunita Kumari; Jat, Raj Kumar (Indian Farming, 2024)
Raised bed planting (RBP) enhances soybean productivity and profitability through improved water and nutrient use efficiency as well as pest control. Despite requiring initial investment and specialized knowledge, its advantages include better yields and sustainability. Capacity building of farmer, providing financial incentives, and conducting on-farm research trials are pivotal for scaling adoption, validating the efficacy of RBP, and mitigating uncertainties across varied climatic conditions.